METHODOLOGY OF USING ARTIFICIAL INTELLIGENCE IN DEVELOPING INNOVATIVE COMPETENCE OF FUTURE PRIMARY EDUCATION TEACHERS - BAXRONOVA SARVINOZ AKBAR QIZI (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: This article discusses the theoretical and practical aspects of the effective use of artificial intelligence technologies in the development of innovative competence of future primary education teachers. Especially for teachers working at the primary education stage, the use of artificial intelligence-based tools is expanding the opportunities for individualizing the teaching process, adapting it to the needs of students, and improving the quality of education. The article analyzes the integration of artificial intelligence technologies into the pedagogical process, the components of the concept of innovative competence, and the methodology for their formation. It also provides practical suggestions, methodological approaches, and ways to improve the teacher training system.